2008
DOI: 10.1016/j.neuroimage.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a fully automated 3D hippocampal segmentation method using subjects with Alzheimer's disease mild cognitive impairment, and elderly controls

Abstract: We introduce a new method for brain MRI segmentation, called the auto context model (ACM), to segment the hippocampus automatically in 3D T1-weighted structural brain MRI scans of subjects from the Alzheimer's Disease Neuroimaging Initiative (ADNI). In a training phase, our algorithm used 21 hand-labeled segmentations to learn a classification rule for hippocampal versus non-hippocampal regions using a modified AdaBoost method, based on ∼18,000 features (image intensity, position, image curvatures, image gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
169
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(182 citation statements)
references
References 63 publications
13
169
0
Order By: Relevance
“…For HC segmentation, recently published results (Barnes et al, 2008;Chupin et al, 2007;Morey et al, 2009;Morra et al, 2008;Pohl et al, 2007;van der Lijn et al, 2008) indicated high kappa index values greater than 0.80. The latest published methods based on the nonlinear warping of the best templates and involving a label fusion step (Collins and Pruessner, 2010;Gousias et al, 2008;Lotjonen et al, 2010) obtained kappa index values equal to or greater than 0.88.…”
Section: Discussionmentioning
confidence: 95%
“…For HC segmentation, recently published results (Barnes et al, 2008;Chupin et al, 2007;Morey et al, 2009;Morra et al, 2008;Pohl et al, 2007;van der Lijn et al, 2008) indicated high kappa index values greater than 0.80. The latest published methods based on the nonlinear warping of the best templates and involving a label fusion step (Collins and Pruessner, 2010;Gousias et al, 2008;Lotjonen et al, 2010) obtained kappa index values equal to or greater than 0.88.…”
Section: Discussionmentioning
confidence: 95%
“…Although this is inevitable in the case of amyloid imaging where the only FDA-and EMA-approved procedure is structured visual rating, a number of automated or semiautomated tools are available for structural MR and FDG-PET [36][37][38][39][40]. However, despite their demonstrated superiority over visual assessments [28][29][30]41,42], these more quantitative measures are used by a minority of centers.…”
Section: Discussionmentioning
confidence: 99%
“…CDF plots, based on the above correlation tests, were used to rank the proportion of significant voxels in association with SNP rs3751812, BMI, and WMB (Fig. S3) (24,25,51). See SI Text.…”
mentioning
confidence: 99%